LGALS3 (galectin 3) mediates an unconventional secretion of SNCA/α-synuclein in response to lysosomal membrane damage by the autophagic-lysosomal pathway in human midbrain dopamine neurons. Issue 5 (4th May 2022) - Burbidge, Kevin; Rademacher, David J.; Mattick, Jessica; Zack, Stephanie; Grillini, Andrea; Bousset, Luc; Kwon, Ochan; Kubicki, Konrad; Simon, Alexander; Melki, Ronald; Campbell, Edward M.
ABSTRACT: Numerous lines of evidence support the premise that the misfolding and subsequent accumulation of SNCA/α-synuclein (synuclein alpha) is responsible for the underlying neuronal pathology observed in Parkinson disease (PD) and other synucleinopathies. Moreover, the cell-to-cell transfer of these misfolded SNCA species is thought to be responsible for disease progression and the spread of cellular pathology throughout the brain. Previous work has shown that when exogenous, misfolded SNCA fibrils enter cells through endocytosis, they can damage and rupture the membranes of their endocytotic vesicles in which they are trafficked. Rupture of these vesicular membranes exposes intralumenal glycans leading to galectin protein binding, subsequent autophagic protein recruitment, and, ultimately, their introduction into the autophagic-lysosomal pathway. Increasing evidence indicates that both pathological and non-pathological SNCA species undergo autophagy-dependent unconventional secretion. While other proteins have also been shown to be secreted from cells by autophagy, what triggers this release process and how these specific proteins are recruited to a secretory autophagic pathway is largely unknown. Here, we use a human midbrain dopamine (mDA) neuronal culture model to provide evidence in support of a cellular mechanism that explains the cell-to-cell transfer of pathological forms of SNCA that are observed in PD. We demonstrate that LGALS3 (galectin 3) mediates the release of SNCA following vesicular damage. SNCA release is also dependent on TRIM16 (tripartite motif containing 16) and ATG16L1 (autophagy related 16 like 1), providing evidence that secretion of SNCA is mediated by an autophagic secretory pathway.